Fabrication of DNA origami lattice on silicon surface for DNA-assisted lithography - Järvinen, Heini (2022)
Metamaterials obtain new properties from having metallized nanoscale features that are often arranged in repeating patterns. In particular, there is a need to create metasurfaces with a negative refractive index. As nanoscale fabrication using conventional top-down methods can be both difficult and time-consuming, bottom-up techniques have gained growing interest. Especially, the DNA origami method can be utilized to assemble lattices with nanoscale features on 2D surfaces, which can then be metallized using DNA-assisted lithography (DALI). This thesis provides a full study of the DNA origami fishnet lattice assembly kinetics and optimization of lattice order on a silicon surface using liquid and air AFM imaging. Similar studies have only been performed on mica, which is unsuitable for the lithographic processes used in DALI. A fishnet lattice with nanoscale features was assembled on silicon utilizing the blunt-ended, twist-corrected Seeman tile (TC-ST) origami and ionic interactions on a solid-liquid interface. In total, the effect of six different cations (Mg2+, Ni2+, Ca2+, Na+, K+, Li+) on DNA origami attachment and lattice quality were studied, out of which magnesium (Mg2+) and sodium (Na+) produced the best quality monolayer. Additionally, for dried samples nickel (Ni2+) was found to be essential for fixing the formed structures on silicon to avoid the detachment of DNA origami during washing. Also, the effect of temperature was found to be crucial for utilizing lower ionic concentrations like the ones employed on mica. Alternatively, the amount of blunt-end interactions between origami can be decreased to work in lower temperatures. In conclusion, similar fishnets with polycrystal-like lattice domains can be produced on silicon as what can be created on mica.